AMBIGUITY OF MEANING IN ENGLISH ADVERTISEMENTS - Sastaparamitha, Ni Nyoman Ayu J.; Martarini, Ni Made Lisma (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTThis study of ‘Ambiguity of Meanings in English Advertisements’ aims to find the causes ofambiguity of meanings in English advertisement. The effect of the ambiguity of meaningsprovides the description about how the ambiguity of meanings affects the readers. The data werecollected through various electronic advertisements in websites. There are five advertisementschosen with priority on their verbal elements, which are the headlines and also the completeelement of advertisements which support the ambiguity of meanings that lies behind theheadline. Data was analysed qualitatively based on the main theory by Myers and Ullmann. Inhis Ullmann’s theory proposes three forms of ambiguity relating to lexical factors as the mostimportant type. The analysis of the cause of ambiguity of meanings is based on the definitiongiven by Myers, while the analysis of the effect of the ambiguity of meanings based on theresearch was done by Myers and Dyer. The results of the analysis indicate that eachadvertisement has its own reason about the cause of ambiguity of meanings in the headlines andsignature. From four advertisements, one is caused by homonymy (plate 4 ); two of the othersare caused by puns and homonymy (plate 1& 2); and the last is caused by metaphor (plate 3).The effects of ambiguity of meanings are dealing with the aims of the advertisementsthemselves, such as to bring emotive associations of a product, to create product or companyimage through the advertisement.Keywords: linguistic, ambiguity, advertisementABSTRAKPenelitian tentang ‘ Makna Ganda dalam Iklan Bahasa Inggris’ bertujuan untuk menemukanpenyebab adanya makna ganda tersebut. Akibat yang terjadi dari makna ganda ini memberikangambaran tentang bagaimana iklan tersebut mempengaruhi pembacanya. Semua datadikumpulkan dari iklan elektronik yang ada di website. Ada empat iklan yang dipilih denganprioritas pada bagian utamanya yaitu headline dan bagian iklan lainnya yang mendukungheadline dari iklan tersebut. Teori utama yang digunakan menganalisa iklan –iklan ini adalahdari Myers dan Ullman yang dianalisis secara qualitatif. Teori Ullman merumuskan ada tigabentuk makna ganda yang disebabkan oleh faktor leksikal merupakan paling penting. Analisispenyebab dari makna ganda pada iklan didasarkan pada definisi yang diberikan oleh Myers,sedangkan untuk menganalisa efeknya terhadap para pembaca didasarkan pada penelitianyang dilakukan oleh Myers dan Dyer. Hasil analisis menunjukkan bahwa setiap iklan memilikialasan tersendiri tentang penyebab makna gandanya pada bagian headline dan signature (cirikhas). Dari keempat iklan yang dianalisis, satu iklan makna gandanya disebabkan olehhomonim, (gambar 4 ); dua iklan berikutnya disebabkan oleh permainan kata-kata (puns) danhomonim ( gambar 1& 2); dan yang terakhir penyebabnya adalah metafora (gambar 3). Efekdari makna ganda berkaitan dengan tujuan dari iklan tersebut, misalnya ingin menarik emosipembaca ke produk yang diiklankan, membuat imej atau kesan tentang produk atau perusahaanmelalui iklan.Kata kunci : bahasa, makna ganda, iklan